Kecerdasan Emosi dan Organizational citizenship behavior Pada Perawat Rumah Sakit - Adelleatemia Adelleatemia; Siti Mulyani (Empathy : Jurnal Fakultas Psikologi, 2022)
Emotional Intelligence andan Organizational citizenship behavior On Hospital NursesThe research aims to find out the relation between emotional intelligence and organizational citizenship behavior. The subjects of this study were nurses at Private Hospital in Yogyakarta. Methods of data collection using quantitative methods. Data collection uses organizational citizenship behavior scale and emotional intelligence scale. The data analysis technique used is Pearson's product moment correlation with the help of the computer program SPSS version 17.00 for Window. Product moment correlation analysis resulted (r) of 0.659 with a significance level of 0.000 with p <0.001 which means that there is a very significant positive relationship between emotional intelligence and organizational citizenship behavior.  Based on the results of the study, it can be said that the correlation coefficient between emotional intelligence variables and organizational citizenship behavior indicates that the hypothesis can be accepted, where the higher the emotional intelligence, the higher the organizational citizenship behavior, and the lower the organizational intelligence, the lower the organizational citizenship behavior. Emotional intelligence contributes 32.15% to organizational citizenship behavior.